Legorreta y las fábricas Mexicanas: El origen de un lenguaje arquitectónico - Paredes Mier, Juan Pablo (UNIVERSIDAD DE SONORA, 2019)
What is intend is to relate, very briefly, the language of convents and novo Hispanic haciendas in Mexico with the origins of the architectural lexicon of Architect Ricardo Legorreta. Its architecture always linked with the culture and traditions of the people of Mexico ―not only by the use of color― but also by embodying a specific Mexicanity. What defines it as a Mexican arch-space? The conventual architecture of sXVI, sXVII will have care a path of mysticism and reflection; the haciendas of the eighteenth and nineteenth centuries, will be the mediation between rural and modernity. It will be the automotive factories -their first orders-, where Legorreta will reveal all those ontological relations that will print the most relevant basis of his personal lexicon, and that is why we want to call this research as “Espacio Legorreta".